EXPORT AND IMPROVING THE QUALITY OF LIBERICA COFFE AS A STRATEGYTO IMPROVE THE WELFARE OF JAMBI PROVINCE COFFE FARMERS - Heppi Syofya; Ayunilaras Ayunilaras (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Agriculture is an important sector for Indonesia. Because around 30% of the population works in the agricultural industry. Based on data from the United States Department of Agriculture (USDA), global coffee production will reach 170 million per 60 kg of coffee in the 2022-2023 period. Indonesia is listed as the 3rd largest coffee producing country in the world in 2022-2023, having produced 11.85 million coffee. Indonesia is the largest producer and exporter of coffee in Asia, this can be an indication that coffee plants play an important role in the national economy both in terms of financing development and employment opportunities. Jambi Province is one of the coffee producers in Indonesia. Nationally, Jambi Province is in 13th position with a planting area of 25,576 Ha and total production of 12,168 kg. The number of farmers cultivating coffee in Jambi was recorded at 26,704. Coffee productivity in Jambi Province is relatively high, recorded at 812 Kg/Ha, higher than the national average productivity of 736 Kg/Ha. Liberika coffee actually has high economic potential because Liberika coffee products are starting to be liked by consumers because of their distinctive taste. This research is qualitative research with a descriptive approach. Researchers use research data in the form of secondary data obtained from a number of credible sources such as scientific articles, books and a number of other sources that are credible and commonly used in research. These data were analyzed using analytical tools with stages of data collection, data selection, data reduction and drawing conclusions. Keywords: Coffee, Export, Liberica Coffee, West Tanjung Jabung